Application of Sodium Silicate Enhances Cucumber Resistance to Fusarium Wilt and Alters Soil Microbial Communities - Zhou, Xingang; Shen, Yanhui; Fu, Xuepeng; Wu, Fengzhi (Frontiers in Plant Science, 2018)
Exogenous silicates can enhance plant resistance to pathogens and change soil microbial communities. However, the relationship between changes in soil microbial communities and enhanced plant resistance remains unclear. Here, effects of exogenous sodium silicate on cucumber (Cucumis sativus L.) seedling resistance to Fusarium wilt caused by the soil-borne pathogen Fusarium oxysporum f. sp. cucumerinum Owen (FOC) were investigated by drenching soil with 2 mM sodium silicate. Soil bacterial and fungal community abundances and compositions were estimated by real-time PCR and high-throughput amplicon sequencing; then, feedback effects of changes in soil biota on cucumber seedling resistance to FOC were assessed. Moreover, effects of sodium silicate on the growth of FOC and Streptomyces DHV3-2, an antagonistic bacterium to FOC, were investigated both in vitro and in the soil environment. Results showed that exogenous sodium silicate enhanced cucumber seedling growth and resistance to FOC. In bare soil, sodium silicate increased bacterial and fungal community abundances and diversities. In cucumber-cultivated soil, sodium silicate increased bacterial community abundances, but decreased fungal community abundances and diversities. Sodium silicate also changed soil bacterial and fungal communality compositions, and especially, decreased the relative abundances of microbial taxa containing plant pathogens but increased these with plant-beneficial potentials. Moreover, sodium silicate increased the abundance of Streptomyces DHV3-2 in soil. Soil biota from cucumber-cultivated soil treated with sodium silicate decreased cucumber seedling Fusarium wilt disease index, and enhanced cucumber seedling growth and defense-related enzyme activities in roots. Sodium silicate at pH 9.85 inhibited FOC abundance in vitro, but did not affect FOC abundance in soil. Overall, our results suggested that, in cucumber-cultivated soil, sodium silicate increased cucumber seedling resistance to Fusarium wilt by changing soil microbial communities rather than by directly inhibiting the growth of FOC.